Layered oxide positive electrode material and preparation method thereof, positive plate and sodium ion battery
By doping magnesium and calcium into the layered oxide cathode material and using Zr cladding, the O3-P3 phase transition and air stability problems are solved, and the cycling and electrochemical properties of the cathode material are improved.
Patent Information
- Application Number
- CN202411313398.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-17
AI Technical Summary
The presence of strong electrostatic repulsion in the deep desodium state of O3-phase layered oxides causes slippage of transition metal layer, severe O3-P3 phase transition, and H2O and CO2 exposed to air lead to loss of active sodium and electrochemical non- The formation of active residual sodium compounds affects battery performance, and the existing doping and coating processes cannot be completed in one sintering.
By doping a specific content of magnesium into the transition metal layer and a calcium into the Na layer, combining a specific Zr content of the cladding layer to stabilize the structure of the positive electrode material, reduce the side reaction between the matrix and the electrolyte, and improve air stability.
The cycling and electrochemical properties of the cathode material are improved, making it exhibit excellent electrochemical properties at high voltages, and strengthening structural stability and air stability.
Smart Images

Figure CN119153656A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials, and in particular to a layered oxide positive electrode material and a preparation method thereof, a positive electrode sheet and a sodium ion battery. Background Art
[0002] Due to their low price and similar physical and chemical properties to lithium-ion batteries, sodium-ion batteries are widely considered to be ideal candidates for large-scale power storage systems for smart grids. Among them, layered oxides have received widespread attention because they are easy to synthesize, have an adjustable voltage range, and show high specific capacity.
[0003] However, when the O3 phase layered oxide is in a deeply desodiumated state, the strong electrostatic repulsion between the two transition metal layers will cause the transition metal layers to slip, leading to a serious O3-P3 phase transition, especially under high-voltage discharge, the phase transition will be more serious.
[0004] At the same time, the layered oxide cathode material is exposed to air, and the H 2 O and CO 2 Easily absorbed and embedded into the layered structure, through spontaneous Na + / H + The exchange causes loss of active sodium, forming NaOH and Na 2 CO 3 These electrochemically inactive residual sodium compounds will cause slurry gelation and current collector corrosion, which is very unfavorable to subsequent electrode manufacturing and battery performance.
[0005] In addition, the existing doping and coating processes cannot be completed in one sintering.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The first object of the present invention is to provide a layered oxide positive electrode material, which can stabilize the transition metal layer structure by doping a specific content of magnesium into the transition metal layer, and can improve the stability of the Na layer by doping a specific content of calcium into the Na layer. At the same time, by setting a coating layer with a specific Zr content, the structural stability of the positive electrode material can be improved, the side reaction between the base material and the electrolyte can be reduced, and the air stability of the positive electrode material can be improved. Doping and coating can improve the cycle performance of the positive electrode material, so that the positive electrode material has excellent electrochemical performance at high voltage.
[0008] The second purpose of the present invention is to provide a method for preparing a layered oxide positive electrode material. By adding multiple additives such as magnesium source, calcium source and zirconium source at one time, the co-doping coating effect can be achieved after sintering at a specific temperature, wherein the Mg element enters the transition metal layer, the Ca element enters the Na layer, and the Zr element is coated on the surface of the material. The three elements work together to stabilize the structure of the positive electrode material and improve the cycle performance of the positive electrode material.
[0009] The third object of the present invention is to provide a positive electrode sheet.
[0010] A fourth object of the present invention is to provide a sodium ion battery.
[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0012] The present invention first provides a layered oxide positive electrode material, comprising a base material and a coating layer coated on the surface of the base material.
[0013] The chemical formula of the matrix material is Na σ Ni x Fe y Mn z Cu s Mg m Ca n O 2 , among which, 0.90≤σ≤1.05, 0<x≤0.4, 0<y≤0.4, 0<z≤0.5, 0.01≤s≤0.12, 0.001≤m≤0.01, 0.001≤n≤0.01, x+y+z+s=1.
[0014] The coating layer includes a Zr-containing compound.
[0015] The layered oxide positive electrode material is mainly prepared from sodium copper nickel iron manganese oxide, a magnesium source, a calcium source and a zirconium source, wherein the molar amount of magnesium element accounts for a percentage of the molar amount of the sodium copper nickel iron manganese oxide. Mg The molar amount of calcium element accounts for the percentage of the molar amount of the sodium copper nickel iron manganese oxide M Ca The molar amount of zirconium element accounts for the molar amount of sodium copper nickel iron manganese oxide as a percentage of M Zr , the M Mg 、The M Ca and the M Zr Satisfies the following relationship:
[0016] (M Mg +M Ca ) / M Zr =2;
[0017] And M Mg / MCa =[x×ΔH(Ni)+y×ΔH(Fe)+z×ΔH(Mn)+s×ΔH(Cu)] / σ×ΔH(Na); wherein, ΔH(Ni) is the bond energy of Ni-O bond, in kJ / mol; ΔH(Fe) is the bond energy of Fe-O bond, in kJ / mol; ΔH(Mn) is the bond energy of Mn-O bond, in kJ / mol; ΔH(Cu) is the bond energy of Cu-O bond, in kJ / mol; ΔH(Na) is the bond energy of Na-O bond, in kJ / mol.
[0018] Furthermore, the particle size D of the layered oxide positive electrode material is 50 Satisfy 3μm≤D 50 ≤12μm.
[0019] Furthermore, the total carbon and sulfur growth value ΔCS of the layered oxide positive electrode material after being placed for 5 days is ≤1000ppm; wherein, the ΔCS=the sum of the mass fractions of the carbon element and the sulfur element in the layered oxide positive electrode material after being placed for 5 days-the sum of the mass fractions of the carbon element and the sulfur element in the layered oxide positive electrode material before being placed.
[0020] Furthermore, the coating layer comprises zirconium oxide.
[0021] Furthermore, the battery containing the layered oxide positive electrode material has a 1C capacity retention rate of ≥90% after 100 cycles at a voltage of 2.5 to 4.15 V.
[0022] Furthermore, the battery containing the layered oxide positive electrode material has a 0.1C first cycle discharge capacity of ≥150 mAh / g at a voltage of 2.5 to 4.15 V.
[0023] The present invention further provides a method for preparing the layered oxide positive electrode material, comprising the following steps: mixing sodium copper nickel iron manganese oxide, a magnesium source, a calcium source and a zirconium source and sintering at 400 to 900° C. The chemical formula of the sodium copper nickel iron manganese oxide is Na e Ni a Fe b Mn c Cu d O 2 , 0.90<e≤1.05, 0<a≤0.4, 0<b≤0.4, 0<c≤0.5, 0.01≤d≤0.12, a+b+c+d=1.
[0024] Furthermore, the molar amount of magnesium element in the magnesium source accounts for 0.1% to 1% of the molar amount of the sodium copper nickel iron manganese oxide.
[0025] Furthermore, the molar amount of calcium element in the calcium source accounts for 0.1% to 1% of the molar amount of the sodium copper nickel iron manganese oxide.
[0026] Furthermore, the molar amount of zirconium element in the zirconium source accounts for 0.1% to 1% of the molar amount of the sodium copper nickel iron manganese oxide.
[0027] Furthermore, the ratio of the sum of the molar amounts of the magnesium element in the magnesium source, the calcium element in the calcium source and the zirconium element in the zirconium source to the molar amount of the sodium copper nickel iron manganese oxide is ≤1%.
[0028] Furthermore, the particle size D of the magnesium source is 50 0.2~5μm.
[0029] Furthermore, the particle size D of the calcium source is 50 0.2~5μm.
[0030] Furthermore, the particle size D of the zirconium source is 50 0.2~5μm.
[0031] Furthermore, the sintering holding time is 5 to 20 hours.
[0032] Furthermore, the sintering atmosphere includes air atmosphere and / or oxygen atmosphere.
[0033] Furthermore, the sintering further includes the steps of crushing and screening.
[0034] Furthermore, the preparation method of the sodium copper nickel iron manganese oxide comprises: mixing a nickel iron manganese hydroxide precursor, a copper source and a sodium source, or mixing a nickel iron manganese copper hydroxide precursor and a sodium source, followed by calcination.
[0035] Furthermore, the particle size D of the nickel-iron-manganese hydroxide precursor or the nickel-iron-manganese-copper hydroxide precursor is 50 The particle size D of the copper source is 2 to 7 μm; 50 The particle size is 1 to 3 μm; the calcination temperature is 700 to 1200° C., and the holding time is 8 to 30 hours; the calcination atmosphere includes air atmosphere and / or oxygen atmosphere; and the calcination further includes crushing and screening steps.
[0036] The present invention further provides a positive electrode sheet, comprising the layered oxide positive electrode material, or the layered oxide positive electrode material prepared by the method for preparing the layered oxide positive electrode material.
[0037] The present invention also provides a sodium ion battery, comprising the positive electrode sheet.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] The layered oxide positive electrode material provided by the present invention can stabilize the transition metal layer structure by doping a specific content of magnesium into the transition metal layer, and can improve the stability of the Na layer by doping a specific content of calcium into the Na layer. In addition, by setting a coating layer with a specific Zr content, the structural stability of the positive electrode material can be improved, the side reaction between the base material and the electrolyte can be reduced, and the air stability of the positive electrode material can be improved. Doping and coating can improve the cycle performance of the positive electrode material, so that the positive electrode material has excellent electrochemical performance at high voltage. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0041] Figure 1 EPMA image of the Zr element of the layered oxide positive electrode material prepared in Example 1 provided by the present invention;
[0042] Figure 2 EPMA image of the Mg element of the layered oxide positive electrode material prepared in Example 1 provided by the present invention;
[0043] Figure 3 EPMA image of the Ca element of the layered oxide positive electrode material prepared in Example 1 provided by the present invention;
[0044] Figure 4 EPMA image of the Ca element of the layered oxide positive electrode material prepared in Comparative Example 5 provided by the present invention;
[0045] Figure 5 This is an EPMA diagram of the Zr element of the layered oxide positive electrode material prepared in Comparative Example 12 provided by the present invention. DETAILED DESCRIPTION
[0046] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0047] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0048] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0049] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.
[0050] In a first aspect, the present invention provides a layered oxide positive electrode material, which includes a base material and a coating layer coated on the surface of the base material.
[0051] The chemical formula of the matrix material is Na σ Ni x Fe y Mn z Cu s Mg m Ca n O 2, where 0.90≤σ≤1.05, 0<x≤0.4, 0<y≤0.4, 0<z≤0.5, 0.01≤s≤0.12, 0.001≤m≤0.01, 0.001≤n≤0.01, x+y+z+s=1. Wherein, σ includes but is not limited to any point value of 0.91, 0.93, 0.95, 0.96, 0.98, 0.99, 1, 1.01, 1.02, 1.03, 1.04, 1.05 or any range value between two of them. x includes but is not limited to any point value of 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4 or any range value between two of them. y includes but is not limited to any one of 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, or any range between them. z includes but is not limited to any one of 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, or any range between them. s includes but is not limited to any one of 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, or any range between them. m includes, but is not limited to, any one of 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, or any range between two values. n includes, but is not limited to, any one of 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, or any range between two values.
[0052] It can be understood that the Mg and Ca elements are doped into the matrix material as doping elements.
[0053] The present invention can promote the fusion of materials during the sintering process and improve the stability of the material structure by controlling the copper content in the positive electrode material to meet 0.01≤s≤0.12.
[0054] The coating layer includes a Zr-containing compound.
[0055] The layered oxide positive electrode material is mainly prepared from sodium copper nickel iron manganese oxide, a magnesium source, a calcium source and a zirconium source, wherein the molar amount of the magnesium element in the magnesium source accounts for a percentage of the molar amount of the sodium copper nickel iron manganese oxide. Mg The molar amount of calcium in the calcium source accounts for a percentage of the molar amount of the sodium copper nickel iron manganese oxide. CaThe percentage of the molar amount of zirconium element in the zirconium source to the molar amount of the sodium copper nickel iron manganese oxide is M Zr , the M Mg 、The M Ca and the M Zr Satisfies the following relationship:
[0056] (M Mg +M Ca ) / M Zr =2.
[0057] And M Mg / M Ca =[x×ΔH(Ni)+y×ΔH(Fe)+z×ΔH(Mn)+s×ΔH(Cu)] / σ×ΔH(Na). It can be understood that the equal sign here can be approximately equal, because the calculated value on the right side of the equal sign may be an infinite decimal. When the calculated value is an infinite decimal, it can be rounded to the nearest integer or rounded to the nearest integer. Among them, the rounding to the nearest integer is to discard the part after the decimal point and only take the integer part, which is different from the rounding method.
[0058] Under the condition of satisfying the above formula, the doping elements Mg and Ca can be evenly distributed inside the material and perfectly combined with the oxygen element.
[0059] Among them, ΔH(Ni) is the bond energy of Ni-O bond, in kJ / mol; ΔH(Fe) is the bond energy of Fe-O bond, in kJ / mol; ΔH(Mn) is the bond energy of Mn-O bond, in kJ / mol; ΔH(Cu) is the bond energy of Cu-O bond, in kJ / mol; ΔH(Na) is the bond energy of Na-O bond, in kJ / mol.
[0060] In some specific embodiments, ΔH(Ni)=391.6 kJ / mol, ΔH(Fe)=409 kJ / mol, ΔH(Mn)=402 kJ / mol, ΔH(Cu)=343 kJ / mol, ΔH(Na)=257 kJ / mol.
[0061] The present invention can stabilize the transition metal layer structure by doping a specific content of magnesium into the transition metal layer; at the same time, calcium element enters the sodium layer to improve the stability of the sodium layer.
[0062] At the same time, the present invention can improve the structural stability of the positive electrode material, reduce the side reaction between the matrix material and the electrolyte, improve the air stability of the positive electrode material, and increase the discharge capacity by providing a coating layer with a specific Zr content.
[0063] The present invention simultaneously performs doping and coating modification, which can improve both the cycle performance and the discharge capacity of the positive electrode material, so that the positive electrode material has excellent electrochemical performance under high voltage.
[0064] In some specific embodiments, the particle size D of the layered oxide positive electrode material is 50 Satisfy 3μm≤D 50 ≤12μm; including but not limited to any point value of 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm or the range value between any two of them.
[0065] In some specific embodiments, the total carbon and sulfur growth value of the layered oxide positive electrode material placed at room temperature (15-30° C.) for 5 days is ΔCS, where ΔCS≤1000ppm. Wherein, 1wt.%=10000ppm. That is, the layered oxide positive electrode material provided by the present invention has good air stability, and the sum of the mass fractions of carbon and sulfur before and after placement is not much different. The generation of residual alkali such as sodium carbonate is reduced.
[0066] Wherein, the ΔCS=the sum of the mass fractions of carbon and sulfur in the layered oxide positive electrode material after 5 days of storage minus the sum of the mass fractions of carbon and sulfur in the layered oxide positive electrode material before storage.
[0067] In some specific embodiments, the coating layer comprises zirconium oxide.
[0068] In some specific embodiments, the molar amount of the zirconium element in the coating layer accounts for 0.1% to 1% of the molar amount of the base material, including but not limited to any point value of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or any range value between two of them.
[0069] In some specific embodiments, the battery containing the layered oxide positive electrode material has a 1C capacity retention rate of ≥90% after 100 cycles at a voltage of 2.5 to 4.15 V, including but not limited to any point value of 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 95% or any range value between two of them. The battery made of the layered oxide positive electrode material provided by the present invention has excellent cycle stability.
[0070] In some specific embodiments, the 0.1C first-week discharge capacity of a battery containing the layered oxide positive electrode material at a voltage of 2.5 to 4.15V is ≥150mAh / g, including but not limited to any point value of 150mAh / g, 150.5mAh / g, 151mAh / g, 152mAh / g, 153mAh / g, 154mAh / g, 155mAh / g, 156mAh / g, 157mAh / g, 158mAh / g, 159mAh / g, and 160mAh / g or a range value between any two of them. The battery made of the layered oxide positive electrode material provided by the present invention has a high capacity.
[0071] In a second aspect, the present invention provides a method for preparing the layered oxide positive electrode material, comprising the following steps: after uniformly mixing sodium copper nickel iron manganese oxide, a magnesium source, a calcium source and a zirconium source, sintering at 400-900°C, and cooling to obtain the layered oxide positive electrode material. The sintering temperature includes but is not limited to any point value of 400°C, 500°C, 600°C, 700°C, 800°C, 900°C or any range value between two of them. The magnesium source and the calcium source are used as dopants, and the zirconium source is used as a coating agent.
[0072] Sintering at a temperature range of 400-900°C can ensure that the Mg element enters the transition metal layer, the Ca element enters the Na layer, and the Zr element is coated on the surface of the material. That is, Mg and Ca are used as doping elements, and Zr is used as a coating element.
[0073] Wherein, the chemical formula of the sodium copper nickel iron manganese oxide is Na e Ni a Fe b Mn c Cu d O 2, where 0.90<e≤1.05, 0<a≤0.4, 0<b≤0.4, 0<c≤0.5, 0.01≤d≤0.12, a+b+c+d=1. e includes but is not limited to any one of 0.91, 0.93, 0.95, 0.96, 0.98, 0.99, 1, 1.01, 1.02, 1.03, 1.04, 1.05, or any range between them. a includes but is not limited to any one of 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, or any range between them. b includes but is not limited to any one of 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, or any range between them. c includes but is not limited to any one of 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, or any range between them. d includes but is not limited to any one of 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, or any range between them.
[0074] The present invention achieves the effect of co-doping and coating by adding multiple additives such as magnesium source, calcium source and zirconium source at one time after sintering at a specific temperature, wherein the Mg element enters the transition metal layer, the Ca element enters the Na layer, and the Zr element is coated on the surface of the material. The three elements work together to stabilize the structure of the positive electrode material and improve the cycle performance of the positive electrode material.
[0075] It can be understood that according to the following relationship: Mg +M Ca ) / M Zr =2.
[0076] and M Mg / M Ca =[x×ΔH(Ni)+y×ΔH(Fe)+z×ΔH(Mn)+s×ΔH(Cu)] / σ×ΔH(Na).
[0077] Weigh corresponding amounts of magnesium source, calcium source and zirconium source.
[0078] In some specific embodiments, the magnesium source includes a Mg-containing compound, such as Mg(OH) 2 ,MgO,MgCO 3 etc., but not limited to.
[0079] In some specific embodiments, the calcium source includes a Ca-containing compound, such as CaCO 3, CaO, etc., but not limited to these.
[0080] In some specific embodiments, the zirconium source includes a Zr-containing compound, such as ZrO 2 , but not limited to this.
[0081] In some specific embodiments, the molar amount of magnesium element in the magnesium source is 0.1% to 1% of the molar amount of the sodium copper nickel iron manganese oxide, including but not limited to any point value of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or any range value between two of them.
[0082] In some specific embodiments, the molar amount of calcium element in the calcium source is 0.1% to 1% of the molar amount of the sodium copper nickel iron manganese oxide, including but not limited to any point value of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or any range value between two of them.
[0083] In some specific embodiments, the molar amount of the zirconium element in the zirconium source is 0.1% to 1% of the molar amount of the sodium copper nickel iron manganese oxide, including but not limited to any point value of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or a range value between any two of them.
[0084] In some specific embodiments, the sum of the molar amounts of the magnesium element in the magnesium source, the calcium element in the calcium source and the zirconium element in the zirconium source accounts for ≤1% of the molar amount of the sodium copper nickel iron manganese oxide, including but not limited to any one of 0.09%, 0.08%, 0.07%, 0.06%, 0.05%, 0.04%, 0.03%, 0.01% or a range between any two of them.
[0085] The right amount of doping can improve the structural stability. Excessive doping in the transition metal layer will cause the Ni element to precipitate and generate a NiO impurity phase. Excessive doping of the Na layer will cause irreversible precipitation of Na, and the material capacity will be greatly reduced. Excessive coating will cause the Na ion diffusion rate to decrease, affecting the material rate performance. Therefore, the present invention can further improve the material structure stability and reduce the occurrence of side reactions by controlling the doping and coating amounts.
[0086] In some specific embodiments, the particle size D of the magnesium source is 50 It is 0.2 to 5 μm, including but not limited to any point value of 0.2 μm, 0.3 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, and 5 μm, or a range value between any two of them.
[0087] In some specific embodiments, the particle size D of the calcium source is 50 It is 0.2 to 5 μm, including but not limited to any point value of 0.2 μm, 0.3 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, and 5 μm, or a range value between any two of them.
[0088] In some specific embodiments, the particle size D of the zirconium source is 50 It is 0.2 to 5 μm, including but not limited to any point value of 0.2 μm, 0.3 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, and 5 μm, or a range value between any two of them.
[0089] Controlling the particle sizes of the magnesium source, calcium source and zirconium source can make the additives more evenly distributed during the mixing process.
[0090] In some specific embodiments, the sintering holding time is 5 to 20 hours, including but not limited to any one of 5h, 6h, 8h, 10h, 12h, 14h, 15h, 16h, 18h, and 20h or a range between any two of them.
[0091] In some specific embodiments, the sintering heating rate is 1 to 10°C / min, including but not limited to any one of 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 8°C / min, and 10°C / min, or a range between any two of them.
[0092] In some specific embodiments, the sintering atmosphere includes air atmosphere and / or oxygen atmosphere.
[0093] In some specific embodiments, the sintering further includes the steps of crushing and screening.
[0094] In some specific embodiments, the preparation method of the sodium copper nickel iron manganese oxide comprises: mixing a nickel iron manganese hydroxide precursor, a copper source and a sodium source, and then calcining. Alternatively, mixing a nickel iron manganese copper hydroxide precursor and a sodium source, and then calcining.
[0095] In some specific embodiments, the particle size D of the nickel iron manganese hydroxide precursor or the nickel iron manganese copper hydroxide precursor is 50 2 to 7 μm; including but not limited to any point value of 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or a range value between any two of them.
[0096] In some specific embodiments, the particle size D of the copper source is 501 to 3 μm; including but not limited to any point value of 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm or a range value between any two of them.
[0097] By controlling the particle sizes of the nickel-iron-manganese hydroxide precursor, the nickel-iron-manganese-copper hydroxide precursor and the copper source, a positive electrode material with a suitable particle size can be obtained, which is beneficial to improving the electrochemical performance of the positive electrode material.
[0098] In some specific embodiments, the copper source includes a copper-containing compound, such as CuO, but is not limited thereto.
[0099] In some specific embodiments, the calcination temperature is 700-1200°C, including but not limited to any one of 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C or any range between two of them; the holding time is 8-30h, including but not limited to any one of 8h, 10h, 12h, 15h, 18h, 20h, 24h, 26h, 28h, 30h or any range between two of them.
[0100] In some specific embodiments, the heating rate of calcination is 1 to 10°C / min, including but not limited to any one of 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 8°C / min, and 10°C / min, or a range between any two of them.
[0101] In some specific embodiments, the calcination atmosphere includes air atmosphere and / or oxygen atmosphere.
[0102] Optionally (optional or not), the calcination further includes the steps of crushing and screening.
[0103] In a third aspect, the present invention provides a positive electrode sheet, comprising the layered oxide positive electrode material, or the layered oxide positive electrode material prepared by the method for preparing the layered oxide positive electrode material.
[0104] The positive electrode sheet has excellent electrochemical performance and good processing performance.
[0105] Optionally, the positive electrode sheet further includes a binder and a conductive agent, which is not limited in the present invention.
[0106] In a fourth aspect, the present invention provides a sodium ion battery comprising the positive electrode sheet.
[0107] This sodium ion battery has high capacity and excellent cycle performance.
[0108] Optionally, the sodium ion battery further includes a negative electrode sheet, a separator and an electrolyte, which is not limited in the present invention.
[0109] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0110] Example 1
[0111] The method for preparing the layered oxide positive electrode material provided in this embodiment comprises the following steps:
[0112] Weigh the nickel iron manganese hydroxide precursor Ni 0.334 Fe 0.333 Mn 0.333 (OH) 2 (Particle size D 50 4.5μm) 2.0kg, copper oxide (particle size D 50 2μm) 0.054g, that is, the molar amount of copper element accounts for 3% of the nickel iron manganese hydroxide precursor. According to the sodium ratio σ = 1.00, weigh 1.224kg of sodium carbonate (purity of 99.75%), mix the above raw materials evenly, and calcine them at 960℃ in air atmosphere for 24h at a heating rate of 4℃ / min. After cooling, crush and sieve to obtain a particle size D 50 8μm sodium copper nickel iron manganese oxide NaNi 0.3298 Fe 0.3201 Mn 0.3201 Cu 0.03 O 2 .
[0113] Weigh the magnesium source, calcium source and zirconium source according to the following relationship: (M Mg +M Ca ) / M Zr =2,M Mg / M Ca =[x×ΔH(Ni)+y×ΔH(Fe)+z×ΔH(Mn)+s×ΔH(Cu)] / σ×ΔH(Na), where ΔH(Ni)=391.6 kJ / mol, ΔH(Fe)=409 kJ / mol, ΔH(Mn)=402 kJ / mol, ΔH(Cu)=343 kJ / mol, ΔH(Na)=257 kJ / mol; magnesium source is Mg(OH) 2 , particle size D 50 2.5 μm, where the molar amount of magnesium accounts for the percentage of the molar amount of sodium copper nickel iron manganese oxide M Mg=0.3%; calcium source is CaCO 3 , particle size D 50 2.5 μm, where the molar amount of calcium accounts for the percentage of the molar amount of sodium copper nickel iron manganese oxide M Ca =0.2%; zirconium source is ZrO 2 , particle size D 50 2.5 μm, where the molar amount of zirconium element accounts for the percentage of the molar amount of sodium copper nickel iron manganese oxide M Zr =0.25%. Then, after the sodium copper nickel iron manganese oxide is evenly mixed with the magnesium source, calcium source and zirconium source, it is sintered at 700°C in an air atmosphere for 18 hours at a heating rate of 4°C / min, and then crushed and sieved after cooling to obtain a particle size D 50 It is a layered oxide positive electrode material with a diameter of 9.34μm.
[0114] The layered oxide positive electrode material comprises a matrix material and ZrO 2 The chemical formula of the coating layer and the base material is: NaNi 0.3298 Fe 0.3201 Mn 0.3201 Cu 0.03 Mg 0.003 Ca 0.002 O 2 .
[0115] Among them, [x×ΔH(Ni)+y×ΔH(Fe)+z×ΔH(Mn)+s×ΔH(Cu)] / σ×ΔH(Na)=(0.3298×391.6+0.3201×409+0.3201×402+0.03×343) / 257=1.5; M Mg / M Ca =0.3% / 0.2%=1.5; (M Mg +M Ca ) / M Zr =(0.3%+0.2%) / 0.25%=2.
[0116] Example 2
[0117] The preparation method of the layered oxide positive electrode material provided in this embodiment is basically the same as that in Example 1, except that the nickel iron manganese hydroxide precursor and copper oxide are replaced by nickel iron manganese copper hydroxide precursor Ni 0.324 Fe 0.323 Mn 0.323 Cu 0.030 (OH) 2 (Particle size D 50 is 4.5μm), and the quality of sodium carbonate is adjusted adaptively.
[0118] Example 3
[0119] The preparation method of the layered oxide positive electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that the corresponding mass of sodium carbonate is weighed according to the sodium ratio δ=1.05.
[0120] Example 4
[0121] The preparation method of the layered oxide positive electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that a corresponding mass of sodium carbonate is weighed according to the sodium ratio δ=0.9.
[0122] Example 5
[0123] The preparation method of the layered oxide positive electrode material provided in this embodiment is basically the same as that in embodiment 1, except that the particle size D of the nickel iron manganese hydroxide precursor is 50 Replaced with 2μm.
[0124] Example 6
[0125] The preparation method of the layered oxide positive electrode material provided in this embodiment is basically the same as that in embodiment 1, except that the particle size D of the nickel iron manganese hydroxide precursor is 50 Replaced with 7μm.
[0126] Example 7
[0127] The preparation method of the layered oxide positive electrode material provided in this embodiment is basically the same as that in embodiment 1, except that the particle size D of the copper oxide is 50 Replaced with 1μm.
[0128] Example 8
[0129] The preparation method of the layered oxide positive electrode material provided in this embodiment is basically the same as that in embodiment 1, except that the particle size D of the copper oxide is 50 Replaced with 3μm.
[0130] Example 9
[0131] The preparation method of the layered oxide positive electrode material provided in this embodiment is basically the same as that in embodiment 1, except that the nickel iron manganese hydroxide precursor is replaced by Ni 0.40 Fe 0.20 Mn 0.40 (OH) 2 (Particle size D 50 is 4.5μm), and the masses of copper oxide and sodium carbonate are adjusted adaptively.
[0132] Example 10
[0133] The preparation method of the layered oxide positive electrode material provided in this embodiment is basically the same as that in embodiment 1, except that the nickel iron manganese hydroxide precursor is replaced by Ni 0.25 Fe0.25 Mn 0.50 (OH) 2 (Particle size D 50 is 4.5μm), and the masses of copper oxide and sodium carbonate are adjusted adaptively.
[0134] Embodiment 11
[0135] The preparation method of the layered oxide positive electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that a corresponding mass of copper oxide is added according to a molar percentage of copper element to the nickel-iron-manganese hydroxide precursor of 11%.
[0136] Example 12
[0137] The preparation method of the layered oxide positive electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that a corresponding mass of copper oxide is added according to a molar percentage of copper element to the nickel-iron-manganese hydroxide precursor of 1%.
[0138] Embodiment 13
[0139] The preparation method of the layered oxide positive electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that the sintering temperature is replaced with 500°C.
[0140] Embodiment 14
[0141] The preparation method of the layered oxide positive electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that the sintering temperature is replaced with 900°C.
[0142] Embodiment 15
[0143] The preparation method of the layered oxide positive electrode material provided in this embodiment is basically the same as that in embodiment 1, except that the percentage of the molar amount of magnesium element to the molar amount of sodium copper nickel iron manganese oxide is M. Mg =0.18%, the molar amount of calcium accounts for the percentage of the molar amount of sodium copper nickel iron manganese oxide M Ca =0.12%, and the percentage of the molar amount of zirconium element to the molar amount of sodium copper nickel iron manganese oxide M Zr =0.15%Add the corresponding mass of Mg(OH) 2 、CaCO 3 and ZrO 2 The chemical formula of the base material of the layered oxide positive electrode material prepared in this embodiment is:
[0144] NeNi 0.3298 Fe 0.3201 Mn 0.3201 Cu 0.03 Mg 0.0018 Ca 0.0012 O2 .
[0145] Among them, [x×ΔH(Ni)+y×ΔH(Fe)+z×ΔH(Mn)+s×ΔH(Cu)] / σ×ΔH(Na)=(0.3298×391.6+0.3201×409+0.3201×402+0.03×343) / 257=1.5;
[0146] M Mg / M Ca =0.18% / 0.12%=1.5; (M Mg +M Ca ) / M Zr =(0.18%+0.12%) / 0.15%=2.
[0147] Example 16
[0148] The preparation method of the layered oxide positive electrode material provided in this embodiment is basically the same as that in embodiment 1, except that the percentage of the molar amount of magnesium element to the molar amount of sodium copper nickel iron manganese oxide is M. Mg =0.39%, the molar amount of calcium accounts for the percentage of the molar amount of sodium copper nickel iron manganese oxide M Ca =0.26%, and the percentage of the molar amount of zirconium element to the molar amount of sodium copper nickel iron manganese oxide M Zr =0.325%Add the corresponding mass of Mg(OH) 2 、CaCO 3 and ZrO 2 The chemical formula of the base material of the layered oxide positive electrode material prepared in this embodiment is:
[0149] NeNi 0.3298 Fe 0.3201 Mn 0.3201 Cu 0.03 Mg 0.0039 Ca 0.0026 O 2 .
[0150] Among them, [x×ΔH(Ni)+y×ΔH(Fe)+z×ΔH(Mn)+s×ΔH(Cu)] / σ×ΔH(Na)=(0.3298×391.6+0.3201×409+0.3201×402+0.03×343) / 257=1.5; M Mg / M Ca =0.39% / 0.26%=1.5; (M Mg +M Ca ) / M Zr =(0.39%+0.26%) / 0.325%=2.
[0151] Comparative Example 1
[0152] The preparation method of the layered oxide positive electrode material provided in this comparative example is basically the same as that of Example 1, except that a corresponding mass of copper oxide is added according to a molar percentage of copper element to the nickel-iron-manganese hydroxide precursor of 20%.
[0153] Comparative Example 2
[0154] The preparation method of the layered oxide positive electrode material provided in this comparative example is basically the same as that of Example 1, except that the corresponding mass of sodium carbonate is weighed according to the sodium ratio δ=0.8.
[0155] Comparative Example 3
[0156] The preparation method of the layered oxide positive electrode material provided in this comparative example is basically the same as that in Example 1, except that the particle size D of the nickel iron manganese hydroxide precursor is 50 Replaced with 8μm.
[0157] Comparative Example 4
[0158] The preparation method of the layered oxide positive electrode material provided in this comparative example is basically the same as that in Example 1, except that the particle size D of the copper oxide is 50 Replaced with 4μm.
[0159] Comparative Example 5
[0160] The preparation method of the layered oxide positive electrode material provided in this comparative example is basically the same as that of Example 1, except that the sintering temperature is replaced with 300°C.
[0161] Comparative Example 6
[0162] The preparation method of the layered oxide positive electrode material provided in this comparative example is basically the same as that in Example 1, except that the molar amount of magnesium element is the percentage M of the molar amount of sodium copper nickel iron manganese oxide. Mg Replaced by 0.2%, the molar amount of calcium accounts for the percentage of the molar amount of sodium copper nickel iron manganese oxide M Ca is replaced by 0.5%, and the molar amount of zirconium element accounts for the molar amount of sodium copper nickel iron manganese oxide as a percentage M Zr Replaced by 0.8%.
[0163] The layered oxide positive electrode material comprises a matrix material and ZrO 2 The chemical formula of the coating layer and the base material is: NaNi 0.3298 Fe 0.3201 Mn 0.3201 Cu 0.03 Mg 0.002 Ca 0.005 O 2 .
[0164] Among them, [x×ΔH(Ni)+y×ΔH(Fe)+z×ΔH(Mn)+s×ΔH(Cu)] / σ×ΔH(Na)=(0.3298×391.6+0.3201×409+0.3201×402+0.03×343) / 257=1.5; M Mg / M Ca =0.2% / 0.5%=0.4, (M Mg +M Ca ) / M Zr =(0.2%+0.5%) / 0.8%=0.875.
[0165] Comparative Example 7
[0166] The preparation method of the layered oxide positive electrode material provided in this comparative example is basically the same as that of Example 1, except that no magnesium source, calcium source and zirconium source are added.
[0167] Comparative Example 8
[0168] The preparation method of the layered oxide positive electrode material provided in this comparative example is basically the same as that of Example 1, except that no zirconium source is added.
[0169] Comparative Example 9
[0170] The preparation method of the layered oxide positive electrode material provided in this comparative example is basically the same as that of Example 1, except that no magnesium source is added.
[0171] Comparative Example 10
[0172] The preparation method of the layered oxide positive electrode material provided in this comparative example is basically the same as that of Example 1, except that no calcium source is added.
[0173] Comparative Example 11
[0174] The preparation method of the layered oxide positive electrode material provided in this comparative example is basically the same as that of Example 1, except that copper oxide is not added.
[0175] Comparative Example 12
[0176] The preparation method of the layered oxide positive electrode material provided in this comparative example is basically the same as that of Example 1, except that the sintering temperature is replaced with 1000°C.
[0177] The particle size D of the layered oxide positive electrode material obtained in each embodiment and each comparative example 50 As shown in Table 1.
[0178] Experimental example
[0179] The layered oxide positive electrode materials prepared in each embodiment and each comparative example were used as active materials, mixed according to the mass ratio of active material: SP: PVDF of 90:5:5, and NMP was added to make a viscous glue, which was coated on aluminum foil and baked in a vacuum drying oven at 120°C for 12h to obtain a positive electrode sheet. A metal sodium sheet was used as a counter electrode, a glass fiber (Waterman) was used as a diaphragm, and 1 mol / L NaPF 6 EC / DMC volume ratio = 1:1 (Alfa) was used as the electrolyte, and 2032 button cells were assembled in an Ar protection glove box.
[0180] Each battery was tested in the voltage range of 2.5-4.15V, cycled at 0.1C for 3 weeks and 1C for 100 weeks. The average discharge capacity of each battery at 0.1C for 3 weeks, the discharge capacity of the first week and 100 weeks of 1C cycle were recorded, and the capacity retention rate of 100 weeks of 1C cycle was calculated. The results are shown in Table 1.
[0181] Table 1 Particle size D of layered oxide cathode materials 50 And electrochemical performance test results
[0182]
[0183]
[0184] By comparing Example 1 and Comparative Example 7 through Table 1, it is found that when no magnesium source, calcium source and zirconium source are added, the cyclability of the material decreases significantly, and the CS growth value increases significantly, indicating that the Mg / Ca / Zr co-doping coating has a significant improvement effect on the material structure maintenance and surface regulation.
[0185] By comparing Example 1 and Comparative Example 8, it can be found that without adding a zirconium source, the material cycle performance is slightly reduced and the CS growth value is significantly increased, indicating that Zr coating has a significant improvement in the surface performance of the material, which can improve the structural strength of the material and reduce the reaction with the electrolyte.
[0186] By comparing Example 1, Example 13, Example 14, Comparative Example 5, and Comparative Example 12, it can be found that within a certain coating temperature range, the material exhibits better electrical properties, maintaining a high cycle retention rate while having a high capacity. However, when the sintering temperature is too low or too high, the electrical properties of the material are significantly reduced. This is because the temperature is too low and calcium or magnesium elements cannot be doped into the material, and the temperature is too high and zirconium elements cannot form a coating layer.
[0187] By comparing Example 2, Example 5, Example 6, Example 9, Example 10, Comparative Example 3 and Comparative Example 4, it can be found that changing the proportion of the main elements of the precursor and the particle size of the precursor within the control range has no obvious effect on the doping and coating effect, but has a certain effect on the particle size of the finished product and the first-week discharge capacity.
[0188] By comparing Example 7, Example 8, Example 11, Example 12, and Comparative Example 1, it can be found that changing the amount of copper source added or the copper source particle size within the control range hardly affects the doping and coating effect. However, in Comparative Example 1, the amount of copper source added is too large, resulting in material fusion, which leads to a significant decrease in discharge capacity.
[0189] By comparing Example 1 and Comparative Example 2, it can be found that too low sodium content will lead to a significant decrease in the discharge capacity of the material.
[0190] By comparing Example 1 and Comparative Example 6, it can be found that since Comparative Example 6 does not satisfy the specific relationship, the additive cannot be uniformly doped and coated, the material structure stability and stability are poor, and the cycle performance is reduced.
[0191] By comparing Example 1 and Comparative Examples 8 to 11, it can be found that there is a synergistic effect between the doping elements magnesium, calcium, copper and the coating element zirconium, and the lack of any of these elements will lead to a decrease in electrochemical performance.
[0192] In addition, if Figure 1 The EPMA diagram of the Zr element of the layered oxide positive electrode material prepared in Example 1 is shown. Figure 2 The EPMA graph of the Mg element of the layered oxide positive electrode material prepared in Example 1 is shown. Figure 3 The EPMA graph of Ca element of the layered oxide positive electrode material prepared in Example 1 is shown. Figure 1-Figure 3 It can be found that at a specific sintering temperature, the elements Ca and Mg evenly enter the interior of the material, and the element Zr evenly covers the surface of the material.
[0193] like Figure 4 The EPMA graph of Ca element of the layered oxide positive electrode material prepared in Comparative Example 5 is shown. Figure 4 It can be found that when the sintering temperature is 300°C, Ca cannot enter the interior of the material, so the stability of the Na layer cannot be improved.
[0194] like Figure 5 The EPMA graph of the Zr element of the layered oxide positive electrode material prepared in Comparative Example 12 is shown. Figure 5 It can be found that when the sintering temperature is 1000°C, Zr enters the interior of the material and cannot act as a coating layer, so the cycle performance is significantly reduced.
[0195] The test method of the above EPMA image is as follows: the layered oxide positive electrode material is cut through an argon ion polisher and subjected to SEM image analysis with an acceleration voltage of 15KV and a magnification of 10K.
[0196] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A layered oxide positive electrode material, characterized in that: It comprises a base material and a coating layer coated on the surface of the base material; The chemical formula of the matrix material is Na σ Ni x Fe y Mn z Cu s Mg m Ca n O2, where 0.90≤σ≤1.05, 0<x≤0.4, 0<y≤0.4, 0<z≤0.5, 0.01≤s≤0.12, 0.001≤m≤0.01, 0.001≤n≤0.01, x+y+z+s=1; The coating layer includes a Zr-containing compound; The layered oxide positive electrode material is mainly prepared from sodium copper nickel iron manganese oxide, a magnesium source, a calcium source and a zirconium source, wherein the molar amount of magnesium element accounts for a percentage of the molar amount of the sodium copper nickel iron manganese oxide. Mg The molar amount of calcium element accounts for the percentage of the molar amount of the sodium copper nickel iron manganese oxide M Ca The molar amount of zirconium element accounts for the molar amount of sodium copper nickel iron manganese oxide as a percentage of M Zr , the M Mg 、The M Ca and the M Zr Satisfies the following relationship: (M Mg +M Ca ) / M Zr =2; And M Mg / M Ca =[x×ΔH(Ni)+y×ΔH(Fe)+z×ΔH(Mn)+s×ΔH(Cu)] / σ×ΔH(Na); wherein, ΔH(Ni) is the bond energy of Ni-O bond, in kJ / mol; ΔH(Fe) is the bond energy of Fe-O bond, in kJ / mol; ΔH(Mn) is the bond energy of Mn-O bond, in kJ / mol; ΔH(Cu) is the bond energy of Cu-O bond, in kJ / mol; ΔH(Na) is the bond energy of Na-O bond, in kJ / mol.
2. The layered oxide positive electrode material according to claim 1, characterized in that: At least one of the following conditions is met: (1) Particle size D of the layered oxide positive electrode material 50 Satisfy 3μm≤D 50 ≤12μm; (2) the total carbon and sulfur growth value ΔCS of the layered oxide positive electrode material after 5 days of storage is ≤1000 ppm; wherein ΔCS=the sum of the mass fractions of carbon and sulfur in the layered oxide positive electrode material after 5 days of storage-the sum of the mass fractions of carbon and sulfur in the layered oxide positive electrode material before storage; (3) The coating layer includes zirconium oxide.
3. The layered oxide positive electrode material according to claim 1, characterized in that: At least one of the following conditions is met: (1) A battery containing the layered oxide positive electrode material has a 1C capacity retention rate of ≥90% after 100 cycles at a voltage of 2.5 to 4.15 V; (2) A battery containing the layered oxide positive electrode material has a 0.1C first cycle discharge capacity of ≥150 mAh / g at a voltage of 2.5 to 4.15 V.
4. The method for preparing a layered oxide positive electrode material according to any one of claims 1 to 3, characterized in that: The steps include: The sodium copper nickel iron manganese oxide, the magnesium source, the calcium source and the zirconium source are mixed and sintered at 400-900° C.; Wherein, the chemical formula of the sodium copper nickel iron manganese oxide is Na e Ni a Fe b Mn c Cu d O2, wherein 0.90<e≤1.05, 0<a≤0.4, 0<b≤0.4, 0<c≤0.5, 0.01≤d≤0.12, a+b+c+d=1.
5. The method for preparing the layered oxide positive electrode material according to claim 4, characterized in that: At least one of the following conditions is met: (1) the molar amount of magnesium in the magnesium source accounts for 0.1% to 1% of the molar amount of the sodium copper nickel iron manganese oxide; (2) the molar amount of calcium in the calcium source accounts for 0.1% to 1% of the molar amount of the sodium copper nickel iron manganese oxide; (3) the molar amount of zirconium element in the zirconium source accounts for 0.1% to 1% of the molar amount of the sodium copper nickel iron manganese oxide; (4) The ratio of the sum of the molar amounts of the magnesium element in the magnesium source, the calcium element in the calcium source and the zirconium element in the zirconium source to the molar amount of the sodium copper nickel iron manganese oxide is ≤1%.
6. The method for preparing the layered oxide positive electrode material according to claim 4, characterized in that: At least one of the following conditions is met: (1) Particle size D of the magnesium source 50 0.2~5μm; (2) Particle size D of the calcium source 50 0.2~5μm; (3) The particle size D of the zirconium source 50 0.2~5μm.
7. The method for preparing the layered oxide positive electrode material according to claim 4, characterized in that: At least one of the following conditions is met: (1) The sintering holding time is 5 to 20 hours; (2) The sintering atmosphere includes air atmosphere and / or oxygen atmosphere; (3) The sintering step further includes crushing and screening steps.
8. The method for preparing the layered oxide positive electrode material according to claim 4, characterized in that: The preparation method of the sodium copper nickel iron manganese oxide comprises: mixing a nickel iron manganese hydroxide precursor, a copper source and a sodium source, or mixing a nickel iron manganese copper hydroxide precursor and a sodium source, and then calcining; Optionally, the particle size D of the nickel-iron-manganese hydroxide precursor or the nickel-iron-manganese-copper hydroxide precursor is 50 The particle size D of the copper source is 2 to 7 μm. 50 The particle size is 1 to 3 μm; the calcination temperature is 700 to 1200° C., and the holding time is 8 to 30 hours; the calcination atmosphere includes air atmosphere and / or oxygen atmosphere; and the calcination further includes crushing and screening steps.
9. A positive electrode sheet, characterized in that: It comprises the layered oxide positive electrode material as claimed in any one of claims 1 to 3, or the layered oxide positive electrode material prepared by the preparation method of the layered oxide positive electrode material as claimed in any one of claims 4 to 8.
10. A sodium ion battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 9.
